ANALISIS PERMASALAHAN IMPLEMENTASI QRIS DAN STRATEGI PROMOSI PADA UMKM SALON DAN UMKM KUE PUKIS JADUL - Oktavianus Anugrah Artha Tri Prayoga (Journal of Innovative and Creativity (Joecy), 2026)
The development of digital technology has driven changes in payment systems and marketing strategies in various business sectors, including Micro, Small, and Medium Enterprises (MSMEs). One form of digital transformation developing in Indonesia is the use of the Quick Response Code Indonesian Standard (QRIS) as a non-cash payment method and the use of digital media as a promotional tool. This study aims to analyze the implementation of QRIS and digital promotion strategies in MSME Salon and MSME Kue Pukis Jadul, identify the obstacles faced, and understand the role of digital technology in supporting business development. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. Research informants consisted of business owners, employees, and customers selected using a purposive sampling technique. The results show that both MSMEs have implemented QRIS as an alternative digital payment, but its use is still not optimal because most customers still prefer cash transactions. The low use of QRIS is influenced by customer habits, lack of digital literacy, and suboptimal socialization from the business. From the promotional aspect, both MSMEs still rely on word of mouth and the use of social media that is not done consistently or planned. These conditions mean that the use of digital technology has not yet had a maximum impact on increasing customer numbers and business growth. Therefore, it is necessary to improve digital literacy, optimize the use of QRIS, and develop a more structured digital promotion strategy to increase the competitiveness and sustainability of MSMEs in the digital era.